Burnout and dropout intention in medical students: the protective role of academic engagement - Alves, Sara Abreu (2022)
Introduction: The infuence of burnout, academic engagement, and their interaction in dropout intention among medical students should be further studied. Current research shows its consequences are relevant, however, there is little understanding on burnout and academic engagement moderation in dropout intention. The current study tested a model that relates the efects of coping strategies, social support satisfaction, general distress on academic engagement, burnout, and dropout intention, on medical students. Methods: Through an online survey a non-probabilistic sample of one Medical Faculty’s 1st- and 2nd-year students was recruited. Cross-sectional data were collected using psychometric instruments (Maslach Burnout Inventory – Student Survey, Social Support Satisfaction Scale for College Students, Brief COPE Scale for College Students, University Student Engagement Inventory, and Depression, Anxiety and Stress Scale), sociodemographic and academic variables, and analyzed using structural equation modeling. Results: 532 students (76% response rate) enrolled in the study. Latent variables structural model presented a satisfactory ft to the data and confrmed the expected negative path between burnout and dropout intention (βDI<-SB=0.430; p<.001) and the latent moderation burnout x engagement (βDI<-SB*SE=-0.218; p<.001). Conclusion: Academic engagement attenuates the impact of burnout on dropout intention, working as a protective factor. Social support satisfaction and adaptive coping are associated with increased levels of academic engagement, and general distress and maladaptive coping are associated with burnout. Medical Schools should develop interventions to prevent dropout intention, tackle students’ stress and academic challenges, and develop their academic engagement levels.